Efektivitas Komunikasi Verbal Dalam Meningkatkan Kegiatan Menghafal Juz Amma pada Taman Pendidikan Anak Usia Dini di Kecamatan Tanjungpura, Kabupaten Langkat - Winanti, Rindy; Kamalia, Kamalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Verbal communication is a form of communication that uses various spoken and written words that are often used by many individuals. Verbal communication can be defined as the process by which speakers communicate verbally with listeners and influence the behavior of recipients. The purpose of this study is how is the application of Verbal Communication in the process of memorizing Juz Amma at TPA in Tanjungpura District?, and how is the effectiveness of Verbal Communication in the process of memorizing Juz Amma at TPA in Tanjungpura District?. A qualitative study method with a descriptive approach is used to identify and implement these goals. Data collection was carried out through direct observation, documentation and interviews. Data analysis was carried out qualitatively which included 3 series of activities together, namely data reduction, and presentation and inference or verification, as well as data validity through source triangulation. Keywords: effectiveness, verbal communication, memorization, Al-Qur'an, Juz Amma